El agua en verso (Notas para una lectura de poemas) - Carvajal Milena, Antonio (Anales de Hidrología Médica, 2007)
The article begins with a study of the word “agua” (water) in Spanish metrics. After that, it considers the aesthetical and symbolical aspects of the water and their use in the tradition of Spanish Poetry (Garcilaso de la Vega, Fray Luis de León, Juan Ramón Jiménez, Pedro Salinas, Federico García Lorca, et caetera). Finally, the author explains the influence of all this tradition in its own poetry.
Keywords: Water; Verse; Fountain; Vitality renewal; Cultural renewal